Synthesis and Characterization Studies of Pure and Co Doped ZnO Nano Thin Films: Studi Sintesis dan Karakterisasi Film Tipis Nano ZnO Murni dan yang Didoping Co - Mahdi, Kareema Hameed; Dahham, Najat A. (Academia Open, 2024)
General Background: Thin-film technology is pivotal in advancing modern optoelectronic devices due to its ability to tailor material properties at the nanoscale. Specific Background: Zinc oxide (ZnO) and cobalt oxide (CoO) are prominent materials in this field, with doping techniques such as cobalt incorporation offering potential enhancements in film properties. Knowledge Gap: The impact of cobalt doping on the structural and optical properties of ZnO thin films remains inadequately explored, particularly concerning varying doping concentrations. Aims: Aims to elucidate the effects of cobalt doping on ZnO thin films' structural and optical characteristics, with concentrations of Zn0.6Co0.4O and Zn0.8Co0.2O compared to pure ZnO and CoO films. Results: Thin films were prepared via spin coating on glass substrates at 3000 rpm for 30 seconds. X-ray diffraction analysis revealed that pure ZnO films possess a hexagonal polycrystalline structure, whereas CoO films exhibit a cubic structure. Doping with cobalt resulted in a decrease in peak intensity at the (111) orientation and an increase in grain size. Optical measurements indicated enhanced transmittance and modified absorbance spectra with increased cobalt content, showing maximum absorbance at short wavelengths and diminished values in the visible region. Reflectivity increased with photon energy before decreasing at higher energies. Novelty: Cobalt doping significantly alters both structural and optical properties of ZnO films, with distinct changes in lattice constants, grain size, and optical behavior, suggesting a potential route for optimizing ZnO-based materials. Implications: Cobalt-doped ZnO films hold promise for improved performance in optoelectronic applications, such as solar cells and sensors, necessitating further research into diverse doping strategies to fully harness their technological potential. Highlights: Cobalt doping alters ZnO thin films' structural and optical properties. Spin coating method used at 3000 rpm for 30 seconds. Enhanced optical properties suitable for optoelectronic applications. Keywords: Thin films, Zinc oxide, Cobalt doping, Optical properties, X-ray diffraction